Lean in : women, work, and the will to lead - Sandberg, Sheryl (New York : Alfred A. Knopf, 2013)
"Thirty years after women became 50 percent of the college graduates in the United States, men still hold the vast majority of leadership positions in government and industry. This means that women's voices are still not heard equally in the decisions that most affect our lives. In this book the author examines why women's progress in achieving leadership roles has stalled, explains the root causes, and offers solutions that can empower women to achieve their full potential. She is the chief operating officer of Facebook and is ranked on Fortune magazine's list of the 50 Most Powerful Women in Business and as one of Time magazine's 100 Most Influential People in the World. In 2010, she gave an electrifying TEDTalk in which she described how women unintentionally hold themselves back in their careers. Her talk, which became a phenomenon and has been viewed more than two million times, encouraged women to "sit at the table," seek challenges, take risks, and pursue their goals with gusto. She digs deeper into these issues, combining personal anecdotes, hard data, and compelling research to cut through the layers of ambiguity and bias surrounding the lives and choices of working women. She recounts her own decisions, mistakes, and daily struggles to make the right choices for herself, her career, and her family. She provides advice on negotiation techniques, mentorship, and building a satisfying career, urging women to set boundaries and to abandon the myth of "having it all." She describes specific steps women can take to combine professional achievement with personal fulfillment and demonstrates how men can benefit by supporting women in the workplace and at home. The book is a call to action and a blueprint for individual growth; it is designed to change the conversation from what women can't do to what they can."--Book jacket.
Introduction : Internalizing the revolution -- The leadership ambition gap : what would you do if you weren't afraid? -- Sit at the table -- Success and likeability -- It's a jungle gym, not a ladder -- Are you my mentor? -- Seek and speak your truth -- Don't leave before you leave -- Make your partner a real partner -- The myth of doing it all -- Let's start talking about it -- Working together toward equality -- Let's keep talking ...
Includes bibliographical references (pages 183-217) and index.
Keywords: Women executives; Leadership in women; Sandberg, Sheryl; 0